PENGARUH PENGGUNAAN GADGET DALAM KEGIATAN BELAJAR DAN MENGAJAR TERHADAP PEMBENTUKAN KARAKTER ANAK GENERASI Y - Delia Puspita Sari; Dinda Trinur Indah Sari; Arita Marini (Bajang Institute, 2023)
This study is a research development aimed at determining the effect of gadgets on the character formation of Generation Y children in learning and teaching activities and whether there is an influence of using gadgets on the character formation of students at SDN Cigudeg 01. This research uses qualitative research methods, namely methods in the form of narratives, interviews, and observation. In this interview, the homeroom teacher and 40 fourth-grade students of SDN Cigudeg 01 involved the emergence of a person's character, it can be seen from the habits one makes in life. In the current era of globalisation, technology is increasingly sophisticated and can support all human activities in education and technology supports teaching and learning activities. Technological progress has become one of the factors that greatly influences the formation of a person's character, including in generation Y children. According to de Jong: 2017, these traits or character traits are at least stable, but can be changed, for example with intensive training . Likewise, various experiences from the environment can influence the formation of student character. So that with certain learning patterns or methods, it is expected to be able to find out the effect of using gadgets on the formation of the character of generation Y children